MENGGAPAI DUNIA DENGAN BERWIRAUSAHA (PENDAMPINGAN SANGGAR KEGIATAN BELAJAR KABUPATEN SUMBAWA KAMPUS II DESA BATU BANGKA) - Erma Suryani; Endang Yusnia; Fatmawati Fatmawati (FKIP Universitas Samawa, 2021)
The purpose of this service activity is to foster an entrepreneurial spirit, understanding in opening a business, and choosing a business that is in accordance with environmental conditions and their respective abilities. Understanding of the correct marketing Business Management. The method used is the delivery of material through lectures and discussions with 5 groups of creative mothers who are members of the SKB fostered group of Sumbawa Regency in collaboration with the Faculty of Teacher Training and Education, Samawa University. The conclusion of this activity is that there is an increased understanding of entrepreneurship for housewives, the ability to open a business and choose a business that is in accordance with their respective environmental conditions, and a group understanding of the correct marketing business management.